The Cusp Plasma Imaging Detector (CuPID) CubeSat Observatory: Mission Overview. Issue 4 (28th April 2021) - Walsh, B. M.; Collier, M. R.; Atz, E.; Billingsley, L.; Broll, J. M.; Connor, H. K.; Chornay, D.; Cragwell, T.; Dobson, N.; Eckert, S.; Einhorn, D.; Gallant, G.; et al.
Abstract: The Cusp Plasma Imaging detector (CuPID) Cube Satellite Observatory is a six‐unit Cube Satellite developed to study macroscale properties of dayside magnetopause reconnection. Reconnection will be studied through imaging spatial and temporal ion dispersion signatures in the magnetospheric cusps. As reconnection enables shocked solar wind plasma to enter the cusp, high charge state solar wind ions will charge‐exchange with Earth's neutral exosphere. This process generates soft X‐rays imaged by the spacecraft. CuPID is in a circular, highly inclined (97.6°), sun‐synchronous, low Earth orbit (550 km), where it views upward through the cusp from its low altitude footprint. The mission carries three science instruments, an energetic (>50 keV) radiation detector, a soft X‐ray (0.1–2 keV) imager, and a body‐mounted magnetometer. The soft X‐ray imager employs a novel, wide field‐of‐view (4.6°) slumped micropore optical element to focus X‐rays. The radiation detector uses collimated micro‐dosimeters with blocking foils to discriminate particle species. The three‐axis magnetometer is part of the attitude determination and control system and has been calibrated to provide scientifically useful data. Plain Language Summary: The Cusp Imaging Plasma Instrument Detector (CuPID) CubeSat Observatory is a small spacecraft designed to study soft X‐rays from space. These X‐rays will not penetrate the Earth's atmosphere, so an observer must make measurements from space, and CuPID will fly in a low altitude (550 km) polar orbit. The spacecraft will carry the first ever wide field‐of‐view soft X‐ray imager into orbit to make measurements of the Earth's space environment in soft X‐rays. Scientifically, soft X‐rays are useful as their intensity and dynamics in the Earth's polar cusps provide a proxy for the driving from the sun's solar wind. The spacecraft packs a modular set of avionics as well as soft X‐ray telescope and radiation sensor into a small 10 cm × 20 cm × 30 cm box. The self‐sustained mission will provide the first regular images of the Earth's magnetic field and space environment in soft X‐rays. Key Points: The Cusp Plasma Imaging detector (CuPID) Cube Satellite Observatory is a small satellite built to study soft X‐rays in space CuPID is a pioneering wide field‐of‐view soft X‐ray imager in orbit CuPID studies solar wind‐magnetosphere coupling and magnetopause reconnection